Transformasi Lansia Menuju Active Ageing melalui RUJAK POLO (Rumah Jaringan Usaha Kerja Produktif) di Yogyakarta - Nani Aprilia; Okimustava; Deni Ismanto; M. Sayuti; Dody Hartanto; Ulaya Ahdiani; Bambang Sudarsono; Yusutria; Nur Kholis; Eko Susanto (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
The transformation of the elderly toward active ageing is a crucial issue as Indonesia’s ageing population continues to grow, posing social and economic challenges. Older adults are often perceived as passive and dependent, whereas with the right approach they can remain productive and independent. This community engagement program empowers seniors through the establishment of RUJAK POLO (Rumah Jaringan Usaha Kerja Produktif – Productive Work Network House) as a hub for training, collaboration, and community-based creative enterprise development.The method applied was Participatory Action Research (PAR), involving 20 seniors in Argosari Hamlet, Sedayu, Bantul, from problem identification to training in eco-printing and crafts, business management mentoring, and participatory evaluation. Results show significant improvement: 80% of participants produced simple products after training (compared to 25% before). They also gained additional monthly income of Rp150,000–Rp300,000 from local market sales.Beyond economic impact, RUJAK POLO strengthened community organization, self-confidence, and social bonds. The program supports active ageing, aligns with SDGs 8 and 11, and serves as a replicable best practice model.